PERTANGGUNGJAWABAN PRESIDEN DAN HUBUNGANNYA DENGAN MAHKAMAH KONSTITUSI MENURUT AMANDEMEN UUD 1945 - Noor Tri Hastuti (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
Power And responsibility of President of Republic Of Indonesia by normative it is true have experienced of the friction from pattern of system of quasi presidential before amendment UUD 1945 to pure system presidential pattern hereafter amendment UUD 1945. However by yuridis is constitutional, second of the pattern hitherto still be executed difficult purely and consequent, because of various factor for example: its his weak domicile and kewenangan institute the State in charge to ask the President responsibility strength is political party importance influence in cabinet compilation. As a result, system of President responsibility in Body Politic Indonesia can be told still stay in the vacuous column.